İHVÂN-I SAFA FELSEFESİNDE SAYILARIN GİZEMİ ÜZERİNE BİR ÇÖZÜM DENEMESİ - Bayram Ali Çetinkaya (Felsefe Dünyası)
Numbers are driving elements of the doctrine of Ikhwan al-Safâ. That is why they were in the grip of relations among numbers and logic analogies in science. In this respect, they saw numbers as connection points and coles between nature and holy texts. Nevertheless, Ikhwan al-Safâ used numbers to find out the secrets about future. Numbers, for them, are key elements to understand the existence in the universe and to attain ultimate reality